Microcrystal delivery by pulsed liquid droplet for serial femtosecond crystallography. Issue 4 (1st April 2016) - Mafuné, Fumitaka; Miyajima, Ken; Tono, Kensuke; Takeda, Yoshihiro; Kohno, Jun-ya; Miyauchi, Naoya; Kobayashi, Jun; Joti, Yasumasa; Nango, Eriko; Iwata, So; Yabashi, Makina
Abstract : A liquid‐droplet injector delivers microcrystals of lysozyme in a pulse‐by‐pulse manner for conducting serial femtosecond crystallography with an X‐ray free‐electron laser. The structure was determined at a resolution of 2.3 Å with low sample consumption. Abstract : A liquid‐droplet injector has been developed that delivers pristine microcrystals to an X‐ray irradiation area for conducting serial femtosecond crystallography (SFX) with an X‐ray free‐electron laser (XFEL). By finely tuning the pulsed liquid droplets in time and space, a high hit rate of the XFEL pulses to microcrystals in the droplets was achieved for measurements using 5 µm tetragonal lysozyme crystals, which produced 4265 indexable diffraction images in about 30 min. The structure was determined at a resolution of 2.3 Å from <0.3 mg of protein. With further improvements such as reduction of the droplet size, liquid droplets have considerable potential as a crystal carrier for SFX with low sample consumption.